THE TRADITION OF REPLYING PANTUN IN THE MARRIAGE CUSTOMS OF THE MALAY COMMUNITY OF DENAI KUALA VILLAGE, PANTAI LABU DISTRICT, DELI SERDANG REGENCY - Ummi Nadra Nasution; Muhammad Faishal; Nasihudin (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
People who want to express joy, merchants offering their wares, and traditional leaders and community leaders of the Malay people have long utilized pantun in various occasions. This study aims to uncover and describe how the tradition of exchanging pantun is carried out in Malay wedding ceremonies in Denai Kuala Village, Pantai Labu Subdistrict, Deli Serdang Regency. To collect data, the researcher directly visited the field and observed the wedding procession among the Malay community in Pantai Labu Subdistrict. This study employs a qualitative approach with a descriptive nature, using a field study method that involves the researcher's active participation. One of the cultural characteristics of the Malay community, particularly in Denai Kuala Village, Pantai Labu Subdistrict, is the pantun tradition, which is always present in various traditional ceremonies. Pantun has become an integral part of the customs and rituals of the Malay community, especially in wedding ceremonies. One form of preserving this tradition is clearly evident in the hempang pintu ceremony. This ceremony takes place when the groom is escorted to the bride's house. Before the groom's entourage arrives, the bride's family will spread a long piece of cloth as a cover for the house door. The cloth may only be opened after a session of pantun exchange between the two parties, accompanied by the exchange of money as part of the traditional requirements. This tradition continues to be practiced over time and remains preserved to this day in Malay weddings in Denai Kuala Village, demonstrating the strong cultural bonds passed down through generations.